Syekh Muhammad Arsyad Al-Banjari dan Kajian Falak Nusantara - Nur Amelia Ridha; Ahmad Izzuddin (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
This paper examines the role of Syekh Muhammad Arsyad al-Banjari in the development of Falak (Islamic astronomy) in South Kalimantan, complementing prior biographical studies and scholarship. The issue addressed is the paucity of research on the historical dissemination of Falak knowledge by indigenous Banjar scholars. Employing a library research methodology, the principal data source is Yusuf Halidi’s Ulama Besar Kalimantan Syekh Muhammad Arsyad al-Banjari. A qualitative content analysis traces Syekh Muhammad Arsyad’s more than three decades of education in Mecca, his corrective interventions regarding qibla orientation in mosques across Batavia, and his initiative to establish an Islamic educational institution in Kampung Dalam Pagar. The findings demonstrate that he mastered thirty-five disciplines, that his treatise Mas’alah al-Qiblah fil-Batawy served as the primary reference for qibla determination in his era, and that he founded a pesantren which produced successive generations of Banjar scholars. These results underscore Syekh Muhammad Arsyad al-Banjari’s pivotal contribution to the Nusantara Falak tradition and highlight the imperative of preserving his manuscript legacy.